Correlation Between SARS-Cov-2 Vaccination, COVID-19 Incidence and Mortality: Tracking the Effect of Vaccination on Population Protection in Real Time - Fukutani, Kiyoshi F.; Barreto, Mauricio L.; Andrade, Bruno B.; Queiroz, Artur T. L. (Frontiers in Genetics, 2021)
Covid 19 has struck the world since the ending of 2019. Tools for pandemic control were scarce, limited only to social distance and face mask usage. Today, up to 12 vaccines were approved and the rapid development raises questions about the vaccine efficiency. We accessed the public database provided by each country and the number of death, active cases, and tests in order to evaluate how the vaccine is influencing the Covid19 pandemic. We observed distinct profiles across the countries and it was related to the vaccination start date and we are proposing a new way to manage the vaccination.